Gamification for Healthcare and Well-being (Global Journal of Medical Research, 2019)
Good health is one's greatest asset. There are many software solutions, developed to help improve the health, and well-being of people, along with them gamified software solutions are popular with their greatest effectiveness and experience compared to physical medication. While there are solutions, developed with the proper understanding of the scientific effect of such solutions to people, some are developed without any scientific analysis or proved results. This paper discusses the main health issues of humans identified within the past decade and what gamification solutions have been implemented to mitigate them and how feasible they have been. Moreover, this article discusses the future development and trends of such gamified solutions for healthcare. Compared to physical treatments and medication, gamification provides an immersive experience with the user's mind strongly connected with the gameplay, which is a great place to improve the health of a person using psychology. Many people enjoy games in their leisure time, and some use them to kill time, but games can be used for much more significant purposes connected with psychology and various functions of the human brain. Some health issues can be cured just by the perception of a person's mind since there are many hormones in the body, which reacts to countless feelings, thoughts, and sensations, that could even cure a person without medicine.
Keywords: Concentration; Health Issues; Gamification; Obesity; Physical; Psychological; Stress